XUV excitation followed by ultrafast non-adiabatic relaxation in PAH molecules as a femto-astrochemistry experiment - Marciniak, Alexandre; Despré, V.; Barillot, T.; Rouzée, Arnaud; Galbraith, M. C. E.; Klei, J.; Yang, C.-H.; Smeenk, C. T. L.; Loriot, V.; Reddy, S. Nagaprasad; Tielens, A. G. G. M.; Mahapatra, S.; et al. (Nature Communications, 2015)
Highly excited molecular species are at play in the chemistry of interstellar media and are involved in the creation of radiation damage in a biological tissue. Recently developed ultrashort extreme ultraviolet light sources offer the high excitation energies and ultrafast time-resolution required for probing the dynamics of highly excited molecular states on femtosecond (fs) (1 fs=10−15s) and even attosecond (as) (1 as=10−18 s) timescales. Here we show that polycyclic aromatic hydrocarbons (PAHs) undergo ultrafast relaxation on a few tens of femtoseconds timescales, involving an interplay between the electronic and vibrational degrees of freedom. Our work reveals a general property of excited radical PAHs that can help to elucidate the assignment of diffuse interstellar absorption bands in astrochemistry, and provides a benchmark for the manner in which coupled electronic and nuclear dynamics determines reaction pathways in large molecules following extreme ultraviolet excitation.